IDENTIFIKASI BAKTERI DARI PUPUK ORGANIK CAIR ISI RUMEN SAPI - Sri Suci Damayanti; Oom Komala; E. Mulyati Effendi (EKOLOGIA, 2018)
Waste treatment technology is not less important for the business of Slaughterhouse (RPH). Various businesses and technologies have been done to handle this waste problem, especially for the rumen waste in RPH. One of them is utilizing the waste as an organic fertilizer. Bovine rumen bacteria are bacteria that originate from the contents of bovine rumen, with simple and inexpensive development techniques. This bacterium helps farmers in improving and developing an insightful agriculture on the preservation of soil fertility and natural resources. The study aims to identify bacteria and find out the diversity, properties, and characteristics of bacteria from the liquid organic content of rumen cows. Methods undertaken by observing colony morphology, colony selection and purification, Gram staining, spores staining, and biochemical testing. Of the four isolates identified there are two bacterial genus, three isolates RS1a, RS2a, RS2b including the genus Bacillus sp. aerobic and an isolates of RS1b including the genus Lactobacillus sp. the facultative of anaerobic. The four isolates of bacteria are able to grow optimum at pH 6.5 and the temperature of 370C is homofermentative.